Association Between Smoking Behavior and Tuberculosis in Indonesia : A Meta-Analysis - Oinike, Aritonang Keshia; Pontoh, Resa Septiani; Tantular, Bertho (Universitas Muhammadiyah Surakarta, 2019)
According to WHO, Pulmonary TB is still one of the most deadly diseases and the death rate has reached millions of lives throughout the world including Indonesia. Smoking is one of the main causes of someone contracting pulmonary TB. The goal of this study is to find association between Pulmonary TB and smoking habits in Indonesia using published study. Published studies that reproting Pulmonary TB and smoking habits was complemented by manual searching. Thirty-six studies were selected that covering 12 province in Indonesia. Meta-analysis was conducted using Random effect model. 46641 patients were included in the analysis, and there were 1698 patients that suffering from Pulmonary TB and 44943 patients that not suffering. The association between Pulmonary TB and smoking habits is statistically significant with <0.0001 in p-value and 4.94 in z-score. The pooled odds ratio estimate for smokersvsnon smokers was of 1.8697dan 95% - CI [1.4583; 2.3972] or patients who smoked 1.86 times at risk of pulmonary TB than non-smoking patients. Smoking habits is significantly associated with the risk of Pulmonary TB in Indonesia.